Outcome of mechanical thrombectomy in the very elderly for the treatment of acute ischemic stroke: the real world experience. (10th September 2015) - To, Chiu Yuen; Rajamand, Sina; Mehra, Ratnesh; Falatko, Stephanie; Badr, Yaser; Richards, Boyd; Qahwash, Omar; Fessler, Richard D
Background: Although initial studies of neuroendovascular intervention did not review benefit over intravenous thrombolytics (iv r-tPA), recent studies have suggested otherwise. Elderly patients (age ≥80 years) are typically excluded from clinical trials. Purpose: To examine the utility of mechanical thrombectomy based on patient outcomes. Material and Methods: All stroke-alert activations at our health system from January 2011 to June 2014 were examined. All patients aged ≥80 years who had undergone mechanical thrombectomy were identified. Clinical characteristics included physiologic imaging findings, use of intravenous thrombolytics, baseline and postoperative National Institute of Health Stroke Scale (NIHSS), thrombolysis in cerebral infarction scores (TICI), and discharge destination. Results: Mean NIHSS on presentation was 18.2 (range, 6–31), and 13.3 (range, 3–30) post thrombectomy. Three (16.6%) patients received iv r-tPA, two (11.1%) had symptomatic intracranial hemorrhage. Eight (44.4%) died, eight (44.4%) were discharged to nursing homes, and two (11.7%) were discharged to inpatient rehab and subsequently home. Favorable outcome was achieved in five (27.7%) patients. Fourteen (77.7%) patients had physiologic imaging prior to intervention. Three (75%) of four patients who did not have physiologic imaging prior to thrombectomy died. Thirteen (66.6%) patients had TICI 3 recanalization. Conclusion: Our study showed that although there remains a role of mechanical thrombectomy in the treatment of acute ischemic stroke in very elderly patients, it is associated with significant higher morbidity and mortality compared to younger patients, but should remain a very viable treatment option when quality of life is the most important consideration.